Mathematical modeling of processes of radiolysis of water, hexane and water–hexane mixture - Agayev, T.N. (Вопросы атомной науки и техники, 2013)
There were carried out modeling of radiolysis processes in the water–hexane system for the purpose of to identify the mechanism of radiolysis and comparison of theoretical and experimental data.